CALCULATION OF THE DRUM BRAKES ON THE REAR WHEELS OF THE CAR SUZUKI ERTIGA 2016 - Aswatul Sahrul; Kardiman -; Aa Santosa (Universitas Muhammadiyah Semarang, 2022)
The brake system is one of the engine component elements in a vehicle that can support the comfort and safety factor in driving. Brakes work to slow down or slow down the movement of the wheels by means of problems. Kinetic energy lost from a moving object is usually converted into heat due to an effect. The purpose of this report is to know the canvas life, function, working principle and efficient calculation. The method used to make reports from direct observations of objects, literature studies and guidance from supervisors. From the specifications of the drum brakes that have been described, we can find out the calculation steps needed to find the normal force on the rear wheel, the permissible frictional force on the asphalt, the life of the canvas with ceramic material, and the maximum spring force at the top and bottom. After several calculation steps, the normal force on the rear wheel will be 2270.50 N. The permissible frictional force on the asphalt is 681.10 N. The service life of the canvas with 100 days of braking for 1.40 seconds is 45 days. The maximum force of the upper spring is 24.99 N, and the maximum force of the lower spring is 166.62 N.